Xanthine Oxidase Inhibitory and Antioxidant Activities of Kasumba Turate and Secang Extracts Combination - Malik, Abd.; Dahlia, Andi Amaliah; Handayani, Virsa; Widiastuti, Harti; San, Htoo Tint; Ahmad, Aktsar Roskiana (Fakultas Farmasi, Universitas Surabaya, 2026)
Kasumba turate flower and Secang lignum have been commonly known as traditional medicinal widely grown in South Sulawesi. Both contain active constituents, including coloring agents such as carthamin in Kasumba turate and brazillin in Secang. These plants have been commonly used in traditional medicine to treat conditions such as high cholesterol, bacterial and viral infections, gout, and as antioxidants. Gout and high cholesterol are closely related. The combination of Kasumba turate and Secang extracts was intended to enhance activity. The evaluation of the xanthine oxidase inhibitor (XOD) and antioxidant activity (AO) was performed using the reducing uric acid and antioxidant FRAP methods. The XOD inhibitory study found that the extracts have activities as follow Sample A, B, C, and Allopurinol of 1.40; 2.1967; 2.24; and 1.39 μg/mL, respectively. The antioxidant capacity of Kasumba turate, Secang extract and their combination was 122.88; 17.36; and 197.31 μg/mL, respectively. We concluded that the combination did not increase the XOD inhibitory and antioxidant capacity. The Kasumba turate extract has the highest activity among the tested extracts.